Collembola Reproduction Decreases with Aging of Silver Nanoparticles in a Sewage Sludge-Treated Soil - McKee, Moira S.; Engelke, Maria; Zhang, Xin; Lesnikov, Elena; Köser, Jan; Eickhorst, Thilo; Filser, Juliane (Frontiers in Environmental Science, 2017)
Silver nanoparticles (AgNP) are integrated into various products due to their antimicrobial characteristics and hence, the application of AgNP is increasing. During production, use and disposal AgNP are emitted and enter the environment via several pathways. Soils are considered a major sink of AgNP. The aim of the present study was to determine the toxic effect of AgNP on Folsomia candida reproduction to illustrate potential impact on terrestrial ecosystems. The AgNP-dependent reduction of F. candida reproduction was studied in RefeSol 01-A, LUFA 2.2 and OECD soil at 0.3 µg – 50 mg Ag kg-1. To simulate realistic exposure pathways, effects on F. candida reproduction after the application of AgNP via sewage sludge and after aging this treatment in the soil for up to 140 days were studied using environmentally relevant concentrations. The OECD representative AgNP, NM-300K, and AgNO3, as a metal salt reference, were used in all experiments. The generated data demonstrate that the presence of AgNP in the soil in the low mg Ag kg-1 concentration range results in significant, but concentration independent inhibition of F. candida reproduction in RefeSol 01-A and LUFA 2.2. Significant inhibition of F. candida reproduction due to AgNP was also observed for soil amended with AgNP treated sludge. An increase in inhibition with aging of the AgNP in the soil was evident. In conclusion, our results demonstrate that, at environmentally relevant concentrations, AgNP adsorption to sludge and subsequent aging in soil lead to a toxic effect on soil invertebrates.